Knowledge, attitudes and beliefs about medical cannabis among the medical students of the Belarus State Medical University - Natallia Khamenka; Uladzimir Pikirenia (Elsevier, 2021)
Cannabis for medical purposes is prohibited in Belarus. Given that some countries have begun prescribing medical cannabis (MC) to certain categories of patients, a cross-sectional study was undertaken at the Belarusian State Medical University (BSMU) to determine the readiness of medical students to use cannabis in their future practice. 333 students responded to the questionnaire to find out their knowledge, attitudes and beliefs about MC. The data were analyzed using Pearson chi-squared test for categorical variables. Findings show most medical students prepared to recommend MC for patient treatment and believe it has benefits for physical or mental health purposes. The survey respondents believe MC can be effective for treatment -23.5 % for glaucoma to 76.9 % for chronic pain. Study results evidence that 83.1 % of the students receive no formal education about medical cannabis and 87.5 % believe professionals should have formal training about the substance.